"n Alternatiewe formulier vir die bevestiging van dienaars van die Woord - Beukes, M. J. de P. (HTS teologiese studies, 2004)
An alternative formulary for the investiture of church ministersThis study aims to present an alternative formulary for the investiture of ministers in the Nederduitsch Hervormde Kerk van Afrika. The new formulary reflects the author’s views that were initially outlined in part and verified by a number of church ministers and congregational members of the church. The article argues for the necessity of a rephrasing of existing formularies, given the current postmodern perceptions of the functions of the church over against the style of the current formulary. Current perceptions of the functions of ministers also necessitate an alternative formulary for the investment of church ministers.